Predictors of Formaldehyde-related Adverse Symptoms Among Laboratory Users in a University in Malaysian Borneo - Emiral, Muhammad Ezmeer; Saupin, Sahipudin; Haron, Fatin Khairah (Malaysian Journal of Medical Sciences, 2026)
Background: Formaldehyde exposure in university laboratories poses significant health risks to students and staff. Understanding the prevalence of adverse symptoms and associated factors is essential for guiding preventive measures. This study assessed the prevalence and predictors of formaldehyde-related adverse symptoms among students and laboratory staff at a university in Malaysian Borneo.Methods: This cross-sectional study employed a validated self-administered questionnaire capturing sociodemographic characteristics, medical and allergy history, exposure frequency, and control measures. Data were analysed using bivariable logistic regression and multivariable logistic regression to identify independent predictors.Results: Among 157 respondents, 34.4% (95% confidence interval [CI]: 27.0, 42.4) reported formaldehyde-related adverse symptoms. The most common complaints were headaches/dizziness (19.1%), unusual tiredness or drowsiness (12.1%), and stress/irritability (7.0%). Five independent predictors were identified: female gender (adjusted odds ratio [aOR]: 3.56; 95% CI: 1.26, 10.10), age ≥ 30 years (aOR: 9.08; 95% CI: 2.33, 35.35), and a history of allergy (aOR: 2.80; 95% CI: 1.09, 7.25). Higher exposure frequency markedly increased symptom risk, with fortnightly (aOR: 7.76; 95% CI: 2.31, 26.09) and weekly formaldehyde handling (aOR: 3.32; 95% CI: 1.05, 10.52) associated with significantly higher odds than monthly exposure. Face mask use showed a strong protective effect (aOR: 0.04; 95% CI: 0.01, 0.10).Conclusion: Given the high prevalence of formaldehyde exposure symptoms, particularly among older individuals, women, individuals with allergy, and frequent handlers, strengthening control measures—particularly consistent mask use and reduction of exposure frequency—should be prioritised to minimise risks in university laboratory settings.